The Relationship between Parenting Style and the Level of Independence of Teenagers at SMPN 1 Tanjung Redeb - Milka DD Pabendan; Sutrisno; Nilam Noorma (PT FORMOSA CENDEKIA GLOBAL, 2023)
Independence is the child's ability to determine attitudes and decisions and be responsible without the help of others. The research aims to determine the relationship between parenting style and the independence of adolescents. Using a descriptive analytic quantitative research type with a cross sectional design with a chi square test on 84 female students. The results of the study obtained data from female respondents (61%), live with parents (86%), parents have jobs (79%), fathers with high school education (49%), mothers with high school education (49%), and have number of siblings 2 people (37%). The majority of adolescents receive authoritative parenting (82%), with the results being very independent (48%), independent (27%), less independent (25%). This shows that the level of independence of adolescent children is influenced by authoritative parenting styles.